Tamarix ramosissima whole plant and leaf level physiological response to increasing salinity - Carter, Jacob (Kansas State University, 2010)
In 1902, President Theodore Roosevelt signed and enacted the Reclamation Act, which would fundamentally alter the lowland hydrology of the arid southwest over the next century. Flow regulations, groundwater pumping, damming, and river channel changes have led to decreases in water table heights and periodic overbank flooding, and subsequently, increased soil salinity in the arid Southwest. During this period, native riparian tree species have declined significantly and an invasive tree species, Tamarix ramosissima, has increased in abundance and distribution. Increases in soil salinity negatively impact the physiology of native riparian tree species, but the impacts of soil salinity on Tamarix physiology are incompletely known. I studied the impact of increasing soil salinities on the physiology of Tamarix in both field and controlled environments. I first studied the impacts of increasing soil salinities on Tamarix physiology at two semi-arid sites in western Kansas. I concluded that physiological functioning in Tamarix was maintained across a soil salinity gradient from 0 to 14,000 ppm illustrating robust physiological responses. Using cuttings from Tamarix trees at both sites, I subjected plants to higher NaCl concentrations (15,000 and 40,000 ppm). Tamarix physiology was decreased at 15,000 ppm and 40,000 ppm. Tamarix physiological functioning was affected at the induction of treatments, but acclimated over 30-40 days. These results reveal a threshold salinity concentration at which Tamarix physiological functioning decreases, but also illustrate the advantageous halophytic nature of Tamarix in these saline environments. Many arid and semi-arid environments are predicted to become more saline, however, results from both studies suggest that increasing salinity will not be a major barrier for Tamarix persistence and range expansion in these environments.
Keywords: Plant physiology; Invasive species; Salinity; Saltcedar; Biology, Plant Physiology (0817)